2022
DOI: 10.3389/fimmu.2021.791983
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hyperuricemia Among Chinese Adults: Findings From Two Nationally Representative Cross-Sectional Surveys in 2015–16 and 2018–19

Abstract: ObjectiveTo determine the nationwide prevalence of hyperuricemia in China and evaluate its trends and associated risk factors.MethodsUsing a multi-stage, stratified, cluster-randomized sampling design, two cross-sectional surveys (representative of national and provincial information) were conducted in 31 provinces (autonomous regions and municipalities) in mainland China, with 166, 861 Chinese adults in 2015–16 and 168, 351 in 2018–19. Serum uric acid (SUA) levels of all participants were measured after a &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 32 publications
(35 reference statements)
4
65
1
Order By: Relevance
“…In Jiangsu adults, the prevalence of hyperuricemia was 13.3% (16.9% in men and 10.3% in women) in 2015 ( 19 ). According to our real-world study, the prevalence of hyperuricemia was 32.6% (34.0% in men and 31.6% in women) among Xiamen population ( Table 1 ), which was higher than that in eastern Chinese population in 2015 and in Chinese adults in 2018–2019 ( 17 19 ). Changes in lifestyle, eating habits and environmental factors are attributed to the development of hyperuricemia ( 20 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In Jiangsu adults, the prevalence of hyperuricemia was 13.3% (16.9% in men and 10.3% in women) in 2015 ( 19 ). According to our real-world study, the prevalence of hyperuricemia was 32.6% (34.0% in men and 31.6% in women) among Xiamen population ( Table 1 ), which was higher than that in eastern Chinese population in 2015 and in Chinese adults in 2018–2019 ( 17 19 ). Changes in lifestyle, eating habits and environmental factors are attributed to the development of hyperuricemia ( 20 ).…”
Section: Discussionmentioning
confidence: 79%
“…The estimated prevalence of hyperuricemia among Chinese adults was 8.4% in 2009–2010 and 14.0% in 2018–2019 ( 16 , 17 ). In Shanghai population, the prevalence of hyperuricemia was 17.2% (22.2% in men and 10.8% in women) in 2015 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, the incidence of HUA has been successively rising worldwide. According to epidemiological surveys, the prevalence of HUA in Chinese adults remarkably rises from 8.4% in 2009–2010 to 14.0% in 2018–2019, and also more than 20.0% from 2007 to 2016 in United States ( 7 , 8 ). Although the serum UA level is not a diagnostic criterion for MetS, longitudinal studies have demonstrated that HUA is closely associated with the development of MetS and its components, and there is a bidirectional relationship between them ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of the economic level and the change in people’s lifestyle and dietary structure, the global incidence and prevalence of hyperuricemia tend to increase steadily. Based on the findings from two nationally representative cross-sectional surveys in 2015–16 and 2018–19, the estimated prevalence of hyperuricemia among Chinese adults is 11.1% ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%